The Effect of Gracilaria Liquid Organic Fertilizer Fermented with Different Starters on the Growth of Pakcoy - Dewi, Eko Nurcahya; Tsaniya, Aulia Rahmawati; Purnamayati, Lukita (Universitas Gadjah Mada, 2024)
This research aimed to determine the effect of adding three different starters, such as Lactobacillus plantarum, Azospirillum sp., and Trichoderma sp., on gracilaria seaweed for bok choy growth. The starter optimized fermentation and improved fertilizer quality in growing bok choy. The seaweed was reduced in size, soaked in 1% phosphoric acid solution, then homogenized and heated with 3% molasses to provide microbial nutrition and 1% KOH to maximize mineral content. Fermentation was carried out for 14 days in the microbial exponential phase for decomposition. The results showed that the addition of L. plantarum and Trichoderma sp. to gracilaria seaweed liquid fertilizer produces the highest values of gibberellin (147 ppm), auxin (140 ppm), and cytokinin (96 ppm). Next, the fertilizer was applied to bok choy to determine the effect on its growth. The highest fresh yield of bok choy was 64.0±1.41 g, the highest chlorophyll A content was 6.70±0.01%, and chlorophyll B was 2.30±0.03%. Even though the control treatment had the highest C/N ratio compared to the other treatments, the highest yields of bok choy freshness, height, and leaf area were found when applying liquid fertilizer with L. plantarum and Trichoderma sp. starter. The study concluded that bok choy growth was significantly encouraged by fertilizer-seaweed with high levels of phytohormones compared to mineral content. Adding L. plantarum and Trichoderma sp. is a good starter for increasing the growth-promoting properties of liquid seaweed fertilizer.